2004
DOI: 10.1021/jm040008+
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Constrained Peptide Analogues of pTyr-Glu-Glu-Ile as Inhibitors of the Src SH2 Domain Binding

Abstract: A series of conformationally constrained peptides were designed and synthesized as the Src SH2 domain ligands based on a tetrapeptide sequence pTyr-Glu-Glu-Ile (pYEEI). In general, the constrained peptides such as compounds 6, 7, and 11 (IC(50) = 1.1-1.5 microM) showed higher binding affinities to the Src SH2 domain relative to the corresponding linear peptides 8a, 9a, and 13a, respectively (IC(50) > 100 microM), and pYEEI (IC(50) = 6.5 microM), as evaluated by a fluorescence polarization assay. Molecular mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…The approximate 10-50-fold higher affinity for monobodies (K d as low as 118 nM) compared to SIM peptides (K d ∼ 4-6 μM; ref. 18) is similar in magnitude to affinity increases for cyclic and disulfide constrained peptides over their linear equivalents (27)(28)(29), supporting our view.…”
Section: Discussionsupporting
confidence: 85%
“…The approximate 10-50-fold higher affinity for monobodies (K d as low as 118 nM) compared to SIM peptides (K d ∼ 4-6 μM; ref. 18) is similar in magnitude to affinity increases for cyclic and disulfide constrained peptides over their linear equivalents (27)(28)(29), supporting our view.…”
Section: Discussionsupporting
confidence: 85%
“…The propensity of the eight octapeptides to assume secondary structures correlated with their inhibitory activities. Previous studies have shown entropy-mediated gains in affinity by constraining the conformational freedom of ligands (37)(38)(39)(40)(41)(42). In the present study, spontaneous prestructuring of the peptide might reduce the entropic penalty associated with formation of a peptide/hTS complex.…”
Section: Resultsmentioning
confidence: 57%
“…The DKP scaffold is widely found in compounds of biological interest and could serve as a drug template with appropriate arrayed pharmacophores. To this point, studies showed that the replacement of a DKP cis-amide bound with structurally similar (z)-alkene units could provide DKP mimetics (16) as novel templates for creating drug-like structures [50][51][52][53][54]. Therefore, adequate linear dipeptide derivatives could act as prodrugs for DKP-based drugs.…”
Section: Peptide Carriers A) Peptide Cyclization and Prodrug Designmentioning
confidence: 99%